2021
DOI: 10.1002/ijc.33591
|View full text |Cite
|
Sign up to set email alerts
|

FOXD1 promotes dedifferentiation and targeted therapy resistance in melanoma by regulating the expression of connective tissue growth factor

Abstract: Metastatic melanoma is an aggressive skin cancer and associated with a poor prognosis. In clinical terms, targeted therapy is one of the most important treatments for patients with BRAF V600E -mutated advanced melanoma. However, the development of resistance to this treatment compromises its therapeutic success. We previously demonstrated that forkhead box D1 (FOXD1) regulates melanoma migration and invasion. Here, we found that FOXD1 was highly expressed in melanoma cells and was associated with a poor surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Moreover, the knockdown of FOXD1 impairs the colony-forming abilities of oral cancer cells after radiation treatment [ 47 ]. Another study showed that upregulated FOXD1 contributed to melanoma cells’ resistance to vemurafenib via the recruited expression of connective tissue growth factor [ 48 ]. In gastric cancer (GC) cells, FOXD1 -AS1 expression induced FOXD1 translation, and these events enhanced GC cell progression and cisplatin resistance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the knockdown of FOXD1 impairs the colony-forming abilities of oral cancer cells after radiation treatment [ 47 ]. Another study showed that upregulated FOXD1 contributed to melanoma cells’ resistance to vemurafenib via the recruited expression of connective tissue growth factor [ 48 ]. In gastric cancer (GC) cells, FOXD1 -AS1 expression induced FOXD1 translation, and these events enhanced GC cell progression and cisplatin resistance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in this article we provide proof that FOXD1 can reliably be used as a biomarker in UM. FOXD1 expression has been assessed in multiple cancer types and is often correlated to a poor prognosis [ 63 , 64 , 65 , 66 ]. In vitro and in vivo experiments elucidated FOXD1 as an oncogene involved in proliferation, dedifferentiation, migration, and radio- and chemoresistance [ 67 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional work on FOXD1 in cutaneous melanoma elucidated its capability to induce the expression of the tumor-specific isoform Rac Family Small GTPase 1B ( RAC1B ) to enhance melanoma migration and invasion [ 38 ]. Additionally, upon BRAF inhibitor treatment, FOXD1 was shown to directly bind the CTGF promoter to promote dedifferentiation and therapy resistance [ 64 ]. In line with published data on EMT, we assessed FOXD1 expression with known EMT inducers and repressors described in squamous cell carcinoma and cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FOXD1 promoted cell proliferation, migration and invasion in colorectal cancer cells by regulating the phosphorylation of ERK 1/2 pathway [ 22 ]. In melanoma, overexpression of FOXD1 enhanced drug resistance of melanoma cells [ 23 ]. Conversely, Woong Ju, et al reported that FOXD1, as a transcription regulating gene, was significantly downregulated in chemoresistant epithelial ovarian cancer [ 24 ].…”
Section: Discussionmentioning
confidence: 99%